'Girls are to be seen, not to be heard': Understanding the Social Trauma of Kutchi Girls in Post-earthquake Gujarat. (September 2013) - Kumar, Manasi
The focus on children in the context of everyday life under vulnerable conditions offers great promise for enriching our understanding of how disputations over culture and forms of belongingness are enacted repeatedly and undramatically: here culture takes a living form rather than a fixed one. The proposed paper is part of a larger project that examines psychological and social trauma of child survivors of the 2001–02 Gujarat earthquake and riots. Interactions with Kutchi girls from villages of Lodai, Khengarpur, Khavda and outskirts of Bhuj enabled the researcher to explore the diverse ways in which gender structures the notions of childhood, household work and domesticity defines their identity, 'inhibition', 'absence' and 'invisibility' of a certain kind were emblematic of their personalities. Keeping these thematics in mind, a critical commentary, Child Attachment Interviews (CAIs) narratives, with girl-survivors of the 2001 Gujarat earthquake is offered. Attachment ( anaclisis, in Greek, meaning dependence/leaning on; in Freudian oeuvre often linked with the problematic of need versus drives) is understood as a basic human survival need, embedded within a dialectical intra-psychic/inter-subjective matrix that pervades culture and socialisation. Girls' impoverished responses during the interviews were marked by long pauses, absent glances, occasional smiles; with mainly monosyllables spoken about their own self though maintaining adultomorphic views of work, their duties and family's expectations. Each interview was more or less a carbon copy of the other. At one level the interviews try to tap into the nature of ties between child and their families, on another level these act as testimonies where differentiating narrative modes of thought from narrative discourse (Bruner, 2004) allowing an exploration into the psychic vicissitudes of this language of absence and everyday existence marked by painful endurance. The paper develops these observations further to argue that trauma in the case of these girls is a continual disenfranchisement of their voices, needs and desires. Attachment trauma in these young girls is this inability and failure of their families to adequately nurture (psychological and social) capabilities (Robeyns, 2003; Sen, 1982) in the (girl) child and this 'lack'/trauma has an intergenerational transmission and import (Grubich-Simitis, 1984; Felman & Laub, 1992). The paper illuminates the symptom these girls have become (being mute, stoic [multiple/ongoing] trauma survivors) and behind this symptom lies social depravities such as gender discrimination and child-rights violation where the mother (and remaining family) is not only implicated but caught in the same rigmarole—of patriarchal hubris.